Consumer preferences for organic wine - Global analysis of people and place. (25th September 2022) - Moscovici, Daniel; Gow, Jeff; Alonso Ugaglia, Adeline; Rezwanul, Rana; Valenzuela, Lionel; Mihailescu, Radu
Abstract: This paper analyzes differences in consumers perception of organic wine and purchasing intentions in traditional/old world wine regions (TPC) compared to new world wine regions (NPC). Our research questions whether consumers would be willing to pay a premium for organic wine, what type of consumer would have a higher likelihood to pay, and if there is a different between TPC and NPC regions. We collect and analyze data from approximately 2500 respondents from seven countries (Australia, Chile, France, Italy, Netherlands, South Africa, and the United States). Our methodology includes descriptive statistics on respondent socio-demographic information, and both a Pearson's chi-squared test and ordinal logistic regression with marginal effects to examine the willingness to pay (WTP) a premium for organic wines. The results show that the respondents are indeed willing to pay more for a wine that is organically labelled whatever their country of origin. We find that the most important consumer attributes include age, importance attributed to eco-certification, and likelihood to buy eco-certified wine. In addition, TPC countries have a slightly higher likelihood to buy and pay a premium for organic wines, compared to NPC countries.